2017
DOI: 10.1039/c7ay00051k
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an LC-MS/MS method for simultaneous quantification of hesperidin and hesperetin in rat plasma for pharmacokinetic studies

Abstract: A simple and sensitive method for the determination of hesperidin and hesperetin was necessary for a pharmacokinetic (PK) study in Wistar rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The six metabolites were identified and included flavonoids known with their excellent antioxidant activities owned to the presence of ortho-dihydroxyl groups and their role in the structure-activity relationship [ 89 ]. The flavonoid 7,3’,4’-trihydroxyisoflavone (3′-hydroxydaidzein) was mentioned before to inhibit the lipid peroxidation in the rat liver with IC50 4.1 µM [ 54 ]. It exerted also the same1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging activity as α-tocopherol and similar antimutagenic activity to 6-hydroxydaidzein [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…The six metabolites were identified and included flavonoids known with their excellent antioxidant activities owned to the presence of ortho-dihydroxyl groups and their role in the structure-activity relationship [ 89 ]. The flavonoid 7,3’,4’-trihydroxyisoflavone (3′-hydroxydaidzein) was mentioned before to inhibit the lipid peroxidation in the rat liver with IC50 4.1 µM [ 54 ]. It exerted also the same1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging activity as α-tocopherol and similar antimutagenic activity to 6-hydroxydaidzein [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, there was a second peak. 42 By comparing the results of their pharmacokinetic studies, we found that eriocitrin, naringin and hesperidin were rapidly absorbed aer oral administration, and all of them showed double peaks, which may be related to their structures; however, further investigation is needed.…”
Section: Pharmacokinetic Studymentioning
confidence: 94%
“…The hesperidin content in samples was identified and quantified using the multiple reaction monitoring mode with the following transition: hesperidin m/z 610.97 → m/z 302.95. 26 The relative content of hesperidin was determined based on the analytical area of sample peaks using an automated peak annotation program in the Waters MassLynx4.1 software (Milford, MA).…”
Section: Quantification Of Hesperidin Content In the Fermented Tea Samplementioning
confidence: 99%